2011
DOI: 10.1007/s00402-011-1433-z
|View full text |Cite
|
Sign up to set email alerts
|

Tibial tubercle advancement osteotomy with bone allograft for patellofemoral arthritis: a retrospective cohort study of 50 knees

Abstract: Tibial tubercle advancement osteotomy can be an effective treatment for anterior knee pain and for patients with arthroscopic evidence of patellar chondral damage. It can provide excellent/good long-term functional results in the majority of patients, with very high satisfaction levels and sustained improvement in pain symptoms. The use of femoral head bone allograft is both effective in obtaining bony union and by definition avoids the donor-site morbidity. Knees with patellar malalignment may also undergo in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In their study, the overall clinical outcomes were rated as excellent/good in 77%, fair in 35%, and poor in 8% of the knees. 12 The modified Fulkerson procedure seems to be an appropriate treatment for overloading around the patella. Because the patella engages in the trochlear groove at approximately 30°–90° of knee flexion, anteriorization of the tibial tubercle may decrease the patellofemoral contact pressure in this functional range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, the overall clinical outcomes were rated as excellent/good in 77%, fair in 35%, and poor in 8% of the knees. 12 The modified Fulkerson procedure seems to be an appropriate treatment for overloading around the patella. Because the patella engages in the trochlear groove at approximately 30°–90° of knee flexion, anteriorization of the tibial tubercle may decrease the patellofemoral contact pressure in this functional range.…”
Section: Discussionmentioning
confidence: 99%
“…After the arthroscopy procedure, we did a standard modified Fulkerson osteotomy; 12,30–32 a longitudinal incision was made from the lower pole of the patella, extending to the base of the tibial tuberosity. The patellar tendon was isolated by sharp dissection along its medial and lateral borders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13) occur in 1 to 2% of patients, most commonly when the transferred fragment is especially thin or short. 40,66 Fractures can also occur in the underlying tibia due to stress riser creation at the distal edge of the osteotomy (►Fig. 14).…”
Section: Distal Patellar Tendon Realignmentmentioning
confidence: 99%
“…PFA is an attractive option for younger patients with isolated patellofemoral disease when considering that the results of extensor mechanism realignment procedures are not uniformly successful -with as many as 35% reported to have persistent pain after surgery. 27 While Meding et al reported more predictable outcomes in younger patients undergoing TKA than undergoing PFA using an earlier component design, improvements in second generation designs have received favorable early reports. 28,29 Longer follow-up will be needed to define the outcomes of this procedure among younger patients who may wish to remain active.…”
Section: Patellofemoral Arthroplastymentioning
confidence: 99%